Northern corridor economic region and logistics industry - Rajandran, Arunan; Sabar, Rohafiz (2012)
The purpose of this paper is to find how NCER improve logistics industry in northern states. A detailed review is used to sort out the literature and develop the research direction of the study.The review is focused on development of logistics industry in northern states including all those researchers which is relevant to logistics industry and important and benefits of NCER. Based on various sources of literature concerning several of projects, developments and new logistics industry are established by NCER. Most of the sources of this study are collected from information system, reports, and research. As a conclusion we can say that improving logistics industry in northern states is very important.